2016
DOI: 10.1007/s12223-016-0449-8
|View full text |Cite
|
Sign up to set email alerts
|

In vitro synergistic effects of chlorpromazine and sertraline in combination with amphotericin B against Cryptococcus neoformans var. grubii

Abstract: Cryptococcus neoformans is encapsulated yeast that causes cryptococcosis. The cryptococcal meningitis may cause neuropsychiatric symptoms. Here, we evaluated the in vitro activity of amphotericin B (AMB), chlorpromazine (CLOR), and sertraline (SERT) alone or in combination against clinical isolates of C. neoformans considering the capsular induction in vitro. Susceptibility tests were carried out using the broth microdilution method in accordance with the CLSI document M27-A3. The combination [CLOR + AMB] exhi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 37 publications
0
24
0
1
Order By: Relevance
“…Despite the diverse mechanism of action of these substances on microorganisms (TET, a 30S ribosomal subunit inhibitor [57]; CLR, a 50S ribosomal subunit inhibitor [58]; AMX, an antibiotic disrupting cell wall synthesis [59]; and MTZ, a genotoxic substance [60]), in the case of all a synergistic/additive interaction with SER was found. The non-selective, positive interaction of SER with many fungicides, including polyenes [15,18,61], echinocandins [15], and azoles [15,17,19,20,23], was also observed in experiments conducted on fungal microorganisms. The ability of this substance to increase the activity of structurally different substances may be related to the potential of SER to inhibit efflux pumps [36,37].…”
Section: Discussionmentioning
confidence: 87%
“…Despite the diverse mechanism of action of these substances on microorganisms (TET, a 30S ribosomal subunit inhibitor [57]; CLR, a 50S ribosomal subunit inhibitor [58]; AMX, an antibiotic disrupting cell wall synthesis [59]; and MTZ, a genotoxic substance [60]), in the case of all a synergistic/additive interaction with SER was found. The non-selective, positive interaction of SER with many fungicides, including polyenes [15,18,61], echinocandins [15], and azoles [15,17,19,20,23], was also observed in experiments conducted on fungal microorganisms. The ability of this substance to increase the activity of structurally different substances may be related to the potential of SER to inhibit efflux pumps [36,37].…”
Section: Discussionmentioning
confidence: 87%
“…There has been recent interest in the use of sertraline to treat cryptococcal meningitis. Sertraline also appears to work synergistically with either amphotericin or fluconazole against C. neoformans in vitro . A (historically) controlled phase 2 trial of this drug in combination with amphotericin and fluconazole appeared promising, suggesting improved rates of clearance of yeast from cerebrospinal fluid, although this contrasted with a smaller controlled trial which found no difference .…”
Section: Discussionmentioning
confidence: 97%
“…In vitro studies have demonstrated synergistic effects with the addition of sertraline or chlorpromazine to amphotericin B for C. neoformans (70). The use of sertraline as an adjunctive therapy for management of cryptococcal meningitis was examined in a recent open-labelled dose finding study.…”
Section: Management Consideration For CD In Hiv-negative Individualsmentioning
confidence: 99%